Relación de arvenses en plantaciones de Tectona grandis L.f. (TECA) y su banco de semillas en la zona central del litoral Ecuatoriano, año 2019. - Chevez Alejandro, Ana Patricia (2019)
The present research project was carried out with the objective of relating the weeds of the teak localed in the cantons Balzar (San Pedro), Santo Domingo (La Palma), Quevedo (San Carlos) and Valencia (Yurac Yacu and El Vergel) and its bank of soil seeds in the central zone of the Ecuadorian cost. The data obtained from the 33 sampling units of the Osorio (2019) and Sánchez (2019) researched were taken into account, where information was recorded on the individuals and species in the different sites for the both the estratum and the seed bank. A total of 43357 individuals, 107 genera and 142 species were identified, with Compositae and Cyperaceae being the most representative families of the sites with 14 and 13 species respectively. It was determined that Cyperus esculentus L. was the most abundant with 3374 individuals, followed by Mecardonia procumbes (Mill.) Small and Veronica persica Poir. with 3174 and 2842 individuals respectively. Regarding the composition of species, herbs predominated (89,07%), native origin (68,31%), perennial cycle (50,63%), dicot type (71,08%), propagation by seed (77,19%) and with antropic dispersion (35,67%). The richness recorded by the Margalef index was averaged with values ranging from 2,44 to 4,53 and the divesity of species calculated by Shannon-Weaver index was 1,71 to 3,23 (average diversity). The analysis of variance has determined that there are no significant differences between low stratum sites and similar seed bank. Keywords: soil seed bank, low estratum, teak, wealth, diversity.